Use Desmos insert y=0.4x into the calculator
Answer:
bx = - 3
Step-by-step explanation:
- 2(bx - 5) = 16
- 2bx + 10 = 16
- 2bx + 10 - 10 = 16 - 10
- 2bx = 6
- 2bx ÷ - 2 = 6 ÷ - 2
bx = - 3
Answer:
Step-by-step explanation:
13
Answer:
Step-by-step explanation:
c. Look for a common factor in each term.
For this case we must solve each of the functions.
We have then:
f (x) = x2 - 9, and g (x) = x - 3
h (x) = (x2 - 9) / (x - 3)
h (x) = ((x-3) (x + 3)) / (x - 3)
h (x) = x + 3
f (x) = x2 - 4x + 3, and g (x) = x - 3
h (x) = (x2 - 4x + 3) / (x - 3)
h (x) = ((x-3) (x-1)) / (x - 3)
h (x) = x-1
f (x) = x2 + 4x - 5, and g (x) = x - 1
h (x) = (x2 + 4x - 5) / (x - 1)
h (x) = ((x + 5) (x-1)) / (x - 1)
h (x) = x + 5
f (x) = x2 - 16, and g (x) = x - 4
h (x) = (x2 - 16) / (x - 4)
h (x) = ((x-4) (x + 4)) / (x - 4)
h (x) = x + 4